Self-regulation as a predictor of Fear of Missing Out in emerging adulthood - Dedy Surya; Dara Aulina (Institut Agama Islam Negeri Langsa, 2020)
The use of social media due to the development of technology has implications for the tendency to know the activity in their social circle. This tendency is called Fear of Missing Out (FoMO). This study aims to determine the relationship between self-regulation and FoMO in emerging adulthood. By using quantitative correlational research methods, this study involved 99 students of Department of Psychology, Malikussaleh University, Aceh, Indonesia with an emerging adulthood age range. The data in this study was collected using two scales, namely Self-Regulation Scale and FoMO Scale. Data analysis using Pearson Correlation. The results showed that there was no significant association between self-regulation variables and FoMO, indicated by the coefficient r = 0.544 and p = 0.000 < 0.05. This result means that there is a negative relationship between self-regulation and FoMO. Self-regulation contributed to FoMO in 4,00%. There were still 96% of other factors related to FoMO tendency. This research showed that self-regulation is too weak to predict FoMO in emerging adulthood